Sustainability reporting and market performance of listed Insurance Firms in Nigeria - Dagunduro, Muyiwa Emmanuel; Falana, Gbenga Ayodele; Ajayi, Joseph Omotoso; Adewara, Yinka Motunrayo; Bello, Seyialade Muyiwa (Universitas Muhammadiyah Malang, 2024)
Purpose: This study examines the effect of sustainability reporting on the market performance of listed insurance firms in Nigeria. Methodology/approach: The study employed an ex-post facto research methodology, using pre-existing, unaltered data from 22 listed Nigerian insurance companies, selected through census sampling. Conducted from 2013 to 2023, the study period covers the transition from the Nigerian Stock Exchange (NSE) to the Nigerian Exchange Group (NGX). Panel regression analysis and the FGLS regression model were used to investigate the relationship between the variables. Findings: This study found that sustainability reporting which includes social, environmental, and governance disclosures positively affects market performance. This shows that the market views a company's comprehensive commitment to sustainability favorably, likely interpreting it as a sign of long-term viability, ethical conduct, and effective risk management. Practical implications: Insurance companies in Nigeria should focus on enhancing and clearly communicating their sustainability reporting initiatives, as these positively impact market performance. Firms should strategically manage and communicate these aspects to better align with investor expectations and highlight their long-term benefits. A balanced and integrated approach to sustainability reporting is essential, as it positively influences market perception and supports long-term growth and stability. Originality/value: This study contributes to the understanding of sustainability reporting within the Nigerian insurance sector. It provides empirical evidence on how different aspects of sustainability reporting: social, environmental, and governance affect market performance. The research fills a critical gap in the literature regarding African insurance markets, offering insights that can inform both academic discourse and practical applications and financial performance.